2022
DOI: 10.37544/0005-6650-2022-01-02-70
|View full text |Cite
|
Sign up to set email alerts
|

Beulverhalten von ringversteiften Kreiszylinderschalen unter Axialdruck – Teil 1: Versuche und geometrische Imperfektionsanalyse/Buckling behavior of ring-stiffened cylinder shells under axial pressure – Part 1: Tests and geometric imperfection analysis

Abstract: Moderne Behälter werden oft als ringversteifte Kreiszylinderschalen ausgeführt. Der traglaststeigernde Effekt eng liegender Ringsteifen unter Axialdruck erfuhr in der Forschung bis heute nur geringe Beachtung. Er ist bisher ungeregelt und infolge unnötig hohen Materialeinsatzes bleiben Stahlbehältern Marktanteile und bessere Nachhaltigkeit verwehrt. Anhand von Versuchen und einer numerischen Studie werden die neuesten Forschungsergebnisse des Einflusses der Ringsteifen auf das Axialbeulverhalten von Kreiszylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, there are two algorithms to further smooth the point cloud and compress its data size. It is possible to unfold the measured point cloud onto a surface and then approximate it using surface fitting techniques, such as the Fourier series [29]. The level of data simplification, smoothing and compression depends on the number of terms in the fitting equation.…”
Section: Case Study 1: Cylindrical Shell Specimenmentioning
confidence: 99%
“…In addition, there are two algorithms to further smooth the point cloud and compress its data size. It is possible to unfold the measured point cloud onto a surface and then approximate it using surface fitting techniques, such as the Fourier series [29]. The level of data simplification, smoothing and compression depends on the number of terms in the fitting equation.…”
Section: Case Study 1: Cylindrical Shell Specimenmentioning
confidence: 99%
“…In his dissertation [3], Jäger-Canás proposed suggestions to address gaps in design standards. More recently, Li and Pasternak et al [43][44][45] presented an investigation of cylindrical ring-stiffened shells based on axial buckling tests and numerical simulations. Several scaled-down welded cylindrical shell specimens with measured geometric imperfections by 3D laser scanning technologies were fabricated, tested, and analyzed based on efficient static analysis with accompanying eigenvalue analysis and high-fidelity numerical calculation (Figure 4).…”
Section: Development and Progress Of The Research In The Areas Of Rin...mentioning
confidence: 99%
“…For unstiffened cylinders, while many different possible buckling shapes can initiate failure at the identical load, ring stiffeners limit the possible failure modes. Moreover, more recent measurement studies [44,45] using 3D laser scanning technology have shown that the initial geometric imperfections of ring-stiffened cylindrical shells are related to the ring stiffener spacing. The results show that the sensitivity of the geometric imperfection is dependent on whether the ring spacing is in multiples of the half-wavelength of the axial buckling of the cylindrical shell.…”
Section: Geometric Imperfection and Sensitivity Of Ring Stiffened Cyl...mentioning
confidence: 99%
“…The main reason for this is that it is difficult to obtain the exact geometric dimensions of the practical shell structure and accurate modelling. Recently, with the continuous development of measurement technology, three-dimensional (3D) scanning technology has been used to directly obtain the actual geometric dimensions of shell specimens [8]. The scanned shell specimen can also be reconstructed in the numerical model.…”
Section: Introductionmentioning
confidence: 99%